2018
DOI: 10.1039/c8cp02190b
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer coupling and electric field tunable electronic properties and Schottky barrier in a graphene/bilayer-GaSe van der Waals heterostructure

Abstract: In this work, using density functional theory we investigated systematically the electronic properties and Schottky barrier modulation in a multilayer graphene/bilayer-GaSe heterostructure by varying the interlayer spacing and by applying an external electric field. At the equilibrium state, the graphene is bound to bilayer-GaSe by a weak van der Waals interaction with the interlayer distance d of 3.40 Å with the binding energy per carbon atom of -37.71 meV. The projected band structure of the graphene/bilayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 81 publications
4
41
0
Order By: Relevance
“…However, heterostructures based on different materials have been designed and studied a lot, with a variety of 2D materials. Vertical heterostructures based on heterogeneous materials have been widely investigated by changing the rotations of different stacking layers [96,97], or the stacking components in consideration of the great quality of the 2D materials [98,99], or the layer thickness [100], or the interlayer spacing [101][102][103], or the stacking mode [104][105][106]. However, while the tunable mechanisms of vertical structures based on different materials have been discussed a lot, the tunable mechanisms of LHSs with different materials are of less concern.…”
Section: Heterogeneous Junctionsmentioning
confidence: 99%
“…However, heterostructures based on different materials have been designed and studied a lot, with a variety of 2D materials. Vertical heterostructures based on heterogeneous materials have been widely investigated by changing the rotations of different stacking layers [96,97], or the stacking components in consideration of the great quality of the 2D materials [98,99], or the layer thickness [100], or the interlayer spacing [101][102][103], or the stacking mode [104][105][106]. However, while the tunable mechanisms of vertical structures based on different materials have been discussed a lot, the tunable mechanisms of LHSs with different materials are of less concern.…”
Section: Heterogeneous Junctionsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] More recently, the main research focus has shied from monocomponent systems to hybrid ones composed of at least two types of chemically different 2D materials, such as graphene/hexagonal boron nitride (h-BN), 8 graphene/black phosphorene (BP), 9 and graphene/transition metal dichalcogenides (TMDs), 10 for the van der Waals (vdW) heterostructure formed between participating materials. This strategy could not only overcome the lattice mismatch-induced defects in participating materials synthesized by epitaxial growth but can also induce excellent physical properties, [11][12][13][14][15][16] thus leading to some very intriguing phenomena such Hofstadter's buttery spectrum, 17,18 strongly bound excitons, 19,20 and spin valley polarization. 21,22 Gallium nitride (GaN) is an important commercial semiconductor for optoelectronic applications in the visible and near-ultraviolet parts of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Our calculated binding energy per carbon atom in the G/MGeS heterostructure at the equilibrium distance is −174 meV. The binding energy is lower than that in graphene/GaSe vdW heterostructure (≈−38 meV) indicating the better stability of this heterostructure. The calculated band structures of the isolated graphene, isolated monolayer GeS, and G/MGeS heterostructure along high symmetry directions in the Brillouin zone (see Figure c) are shown in Figure .…”
Section: Resultsmentioning
confidence: 65%
“…Among various possible heterostructures, graphene‐based vdW heterostructures are attracting much more attention because they can be employed as transparent electrodes, transport and light‐harvesting layers, Schottky junctions, etc. Recently, many ultrathin vdW heterostructures have been fabricated experimentally and investigated theoretically, such as graphene/MoS 2 , graphene/BN, graphene/phosphorene, and graphene/GaSe(S) . These findings have demonstrated that graphene‐based vdW heterostructures have potential applications in nanoelectronic and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%